KEWENANGAN BADAN PENGAWAS OBAT DAN MAKANAN TERHADAP PERDA PROVINSI BALI NO 5 TAHUN 2012 TENTANG PENGENDALIAN PEREDARAN MINUMAN BERALKOHOL - Mahentoro, I Putu (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 2 No 3 (2013), 2013)
ABSTRACT The research was conducted based on the same authority which is owned by the two institutions, namely Food and Drug Administration of the Republic of Indonesia and Bali Provicial Government in monitoring and controlling of alcoholic beverages in Bali. The results of this study demonstrate the Food and Drug Administration and the Provincial Government of Bali have the same authority to supervise and control alcoholic beverages in Bali. Bali Local Government Regulation Number 5 of 2012 on the Circulation of Alcoholic Beverage Control only requires each has a label on alcoholic beverages issued by the Government of Bali has to be distributed to the public, while the authority of the Food and Drug Administration is regulated in the Regulation of Minister of Health of the Republic of Indonesia Number 382/MENKES/PER/VI/1989 on Registration of Food that requires all food produced both by local producers and imported foods are required to be registered to the Ministry of Health through the Food and Drug Administration. In the Regulation Number 5 Year 2012 did not include the authority of the Food and Drug Administration (the Empty Norms) so that the Food and Drug Administration can not perform optimally the law enforcement against manufacturers, distributors and sellers of alcoholic beverages in violation. To cope with the condition it should be a amendment in the Bali Provincial Regulation Number 5 of 2012 by stating firmly and clearly the authority of the Food and Drug Administration related to the registration of food, which requires that for all foods and beverages that will be distributed to the public must be registered to the Ministry of Health through the Food and Drug Administration.
Keywords: Authority; Legal certainty; Alcoholic Beverages